Analysis of serum amino acids and tryptophan metabolites to predict hepatic encephalopathy in portal hypertension patients receiving a transjugular intrahepatic portal shunt (TIPS) - Bao, Li; Lv, Yifan; Yang, Chunjing; Li, Jingfeng; Liu, Fuquan; Shi, Zhengyuan (Frontiers in Pharmacology, 2025)
IntroductionThe incidence of hepatic encephalopathy (HE) after transjugular intrahepatic portal shunt (TIPS) is over 30%, how to decrease the occurrence rate of HE is one of the most challenging issues after TIPS surgery. The aim of this study is to identify the potential biomarker that can predict the occurence of HE after TIPS in patients with portal hypertension (PH), and provide the theoretical support for early clinical diagnosis and prevention.MethodsA total of 50 patients with PH underwent TIPS were enrolled with completed clinical information in this study, and they were divided into two groups with or without the complications of HE.ResultsWe quantitatively determined 20 serum amino acids, and found that 4 amino acid levels were increased significantly in patients who complicated HE after TIPS. Screened by the specific screening criteria (VIP > 1.0; P < 0.05; FC > 1.5, or FC < 0.67) on MetaboAnalyst 5.0 on-line platform, tryptophan (TRP) were identified as the potential biomarker (50.31 μmol/L in non-HE group vs 100.21 μmol/L in HE group). Subsequently the detection of serum tryptophan metabolites revealed that the higher levels of kynurenine (KYN) and 2,3-Pyridinedicarboxylic acid (QA) were observed in the patients complicated HE after TIPS. ROC multivariate analysis indicated that the combination of TRP, KYN and QA provied the better predictive value for HE occurrence in PH patients underwent TIPS (AUC = 0.92).DiscussionThis study provided the theoretical suggestion to the clinical doctor which the level of serum TRP/KYN/QA of patients should be detected before TIPS, and It is of great significance for patient prognosis and reducing the occurrence of HE after TIPS.